2018
DOI: 10.1007/s10899-018-9757-z
|View full text |Cite
|
Sign up to set email alerts
|

Problem and Pathological Gambling in Schizophrenia: Exploring Links with Substance Use and Impulsivity

Abstract: High rates of both problem and pathological gambling (PPG) and substance-use disorders (SUDs) have been reported in schizophrenia, and yet PPG frequently goes undetected in clinical practice and unexamined in research. Here, we aimed to examine the relationship between PPG and SUDs in a large sample of patients across several factors related to both gambling and substance use, including poly-substance use. Additionally, delay discounting is a form of impulsivity known to positively associate with both PPG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 51 publications
2
18
0
Order By: Relevance
“…The SCZ PRS has been shown to be associated with various forms of substance use and dependence (Carey, et al, 2016;Hartz, et al, 2017;Regnisson, et al, 2017). The current findings extend this work, demonstrating that polygenic risk for SCZ associates with a behavioral addiction, DG, that is highly comorbid with substance use disorders in the general population (Kessler, et al, 2008;Petry, et al, 2005) and among individuals with psychosis (Fortgang, et al, 2018). Together, findings to date might indicate that common genetic risk for SCZ confers a general liability to impaired control over rewarding behaviors rather than modulating response to a particular drug or drug class.…”
Section: Discussionsupporting
confidence: 77%
“…The SCZ PRS has been shown to be associated with various forms of substance use and dependence (Carey, et al, 2016;Hartz, et al, 2017;Regnisson, et al, 2017). The current findings extend this work, demonstrating that polygenic risk for SCZ associates with a behavioral addiction, DG, that is highly comorbid with substance use disorders in the general population (Kessler, et al, 2008;Petry, et al, 2005) and among individuals with psychosis (Fortgang, et al, 2018). Together, findings to date might indicate that common genetic risk for SCZ confers a general liability to impaired control over rewarding behaviors rather than modulating response to a particular drug or drug class.…”
Section: Discussionsupporting
confidence: 77%
“…The SCZ PRS has been shown to be associated with various forms of substance use and dependence (Carey, et al, 2016;Hartz, et al, 2017;Regnisson, et al, 2017). The current findings extend this work, demonstrating that polygenic risk for SCZ associates with a behavioral addiction, DG, that is highly comorbid with substance use disorders in the general population (Kessler, et al, 2008;Petry, et al, 2005) and among individuals with psychosis (Fortgang, et al, 2018). Together, findings to date might indicate that common genetic risk for SCZ confers a general liability to impaired control over rewarding behaviors rather than modulating response to a particular drug or drug class.…”
Section: Discussionsupporting
confidence: 77%
“…On the other hand, four studies reported no DD difference between chronic SZ and HC (Avsar et al, 2013;MacKillop & Tidey, 2011;Wing et al, 2012). Specifically, while no group difference was observed between SZ and HC, one study found that pathological and recreational gamblers showed higher DD than non-gamblers within SZ (Fortgang, Hoff & Potenza, 2018). Interestingly, another study found that current and past smokers showed lower DD than nonsmokers in SZ (Wing et al, 2012), a pattern that is the opposite of the gamblers (Wing et al, 2012).…”
Section: Discussionmentioning
confidence: 96%